From Inattentiveness Towards Moral Failures: Acknowledging Simone Weil in Iris Murdoch’s Literary Writings - Braune, Camille (Labyrinth, 2024)
Simone Weil's ideas proved fundamental for Iris Murdoch, opening up a difficult path of thought for one rooted in the British philosophical tradition in the 1950s (Sim 1985, Bok 2005, Lovibond 2011a, Panizza 2022a, Mac Cumhaill and Wiseman 2022). Grasping the Weilian-inspired moral theory of attention sketched by Iris Murdoch is a prerequisite for comprehending the development of her moral ideas (Panizza 2015, Broackes 2012) and the form they may take in her literary writings (Griffin 1993, Morgan 2006). This paper argues that we can read an expression of Simone Weil in Iris Murdoch's novels which articulate her notions of grace and gravity, but also convey the Weilian insights that shape Murdoch's moral perfectionism. It investigates three of Murdoch's well-known male protagonists, i.e., Bradley Pearson, Charles Arrowby and Hilary Burde, so as to comprehend how their moral failures relate to a defective implementation of the concepts of love and attention as theorised by Simone Weil as leading to goodness. Hence, it offers a new examination of the way in which the Murdochian literary staging of inattention as a cause of moral deficiency reveals its Weilian-based ethics of attention.